Digitalization of Agriculture Sector in Nepal: Possibilities and Challenges in the Context of Globalization - Rijal, Lekhnath (CHINTAN-DHARA, 2025)
The transformative potential of digitalization in promoting agricultural entrepreneurship in Nepal, a geographically diversified developing nation with an abundance of natural resources, is examined in this qualitative study. The study, which is based on the Innovation Diffusion Theory (IDT) and the Theory of Planned Behavior (TPB), looks at how digital tools like digital financial systems, e-commerce platforms, and mobile advisory services can boost youth involvement in agribusiness, increase productivity, and improve market access. Secondary data were gathered from government reports, policy documents, peer-reviewed journal articles, and institutional publications using a descriptive and analytical research design. To compile information about the prospects, difficulties, and policy ramifications for digital agriculture and entrepreneurial growth, thematic analysis was used. results show that while Nepal's agricultural sector has a lot of potential, development is hampered by issues like outdated legislation, inadequate training, and a lack of digital infrastructure. In order to address these issues, the report recommends improving internet connectivity in rural areas, implementing capacity-building programs, amending legislation that benefits agriculture, promoting public-private partnerships, and integrating agribusiness into formal education. With the help of these strategic initiatives, Nepal's agricultural landscape can be transformed into a modern, competitive, and sustainable industry. Through the use of digital technology and youth empowerment, Nepal can move closer to inclusive economic growth and food security.